Understanding the nature of crises and risks in the process of ensuring the efficiency of enterprise management - H.Y. Tkachuk; T.О. Biliak; V.G. Vyhovskyi (Економіка, управління та адміністрування)
The article examines the theoretical essence, nature and causes of crises and risks of the enterprise’s economic activity. During the research, it was established that there are currently four approaches to understanding the concept of «crisis» and two conceptual views on «risk». Thus, a crisis is a «non-standard situation or turning point», «aggravation of contradictions in the system’s activity», «deterioration of viability parameters», «cycle phase», and risk, in its turn, is «mathematical expectation of costs from a decision» and «probability of deviation from goals». The causes of contradictions that arise in the process of the enterprise’s economic activity are considered. It is established that they are caused by two mutually determining tendencies of its existence, namely: functioning and development. The functioning of the enterprise restrains development, however, it is its nourishing environment, and development, in its turn, destroys the usual processes of functioning, but creates conditions for better (progressive) functioning. In addition, a number of parameters of the enterprise’s viability (availability of assets, break-even management, liquidity) and the main contradictions arising between the elements of the enterprise’s internal environment and the external environment, which reflect the compliance of internal parameters (prices, quality, volumes of business) with market demand parameters, violation of which leads to crisis phenomena. The division of the causes of crises into external and internal ones has been studied. Among the internal factors, special attention is paid to subjective factors that are the result of risky decisions and ambitions of top managers, which become a fertile environment for the emergence of crisis phenomena at enterprises. This made it possible to draw conclusions about the close relationship between risks and crisis phenomena. Having drawn a parallel between crises and risks, a number of external factors that can become their causes have been established, namely: economic, political, social, administrative-legislative and force majeure. Among the latter, the authors single out those factors that have changed the structure of the concept of force majeure in recent years, namely military aggression and epidemiological factors (bacteriological and viral infections). Having established the correspondence and interrelationship between crises and risks arising in various spheres of the internal environment of the enterprise, we have proposed a number of response measures that can increase the efficiency of enterprise management at the level of each separate sphere.